Genetic diversity of some chili (Capsicum annuum L.) genotypes (International Journal of Agricultural Research, Innovation and Technology, 2014)
A study on genetic diversity was conducted with 54 Chili (Capsicum annuum L.) genotypes through Mohalanobiss D2 and principal component analysis for twelve quantitative characters viz. plant height, number of secondary branch/plant, canopy breadth , days to first flowering, days to 50% flowering, fruits/plant, 5 fruits weight, fruit length, fruit diameter, seeds/fruit, 1000 seed weight and yield/plant were taken into consideration. Cluster analysis was used for grouping of 54 chili genotypes and the genotypes were fallen into seven clusters. Cluster II had maximum (13) and cluster III had the minimum number (1) of genotypes. The highest inter-cluster distance was observed between cluster I and III and the lowest between cluster II and VII. The characters yield/plant, canopy breadth, secondary branches/plant, plant height and seeds/fruit contributed most for divergence in the studied genotypes. Considering group distance, mean performance and variability the inter genotypic crosses between cluster I and cluster III, cluster III and cluster VI, cluster II and cluster III and cluster III and cluster VII may be suggested to use for future hybridization program. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21088 Int. J. Agril. Res. Innov. & Tech. 4 (1): 32-35, June, 2014